Analisis Efektivitas Fasilitas Kemiitraan dalam Mendorong Penanaman Modal di DPMPTSP Kota Serang - Delia Febriyanti; Iin Indriyani; Maskanah Maskanah; Eka Rifianti; Difa Syahrani (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
The Work Practice Program (KKP) is an academic activity aimed at providing students with real work experience while connecting the theories learned in campus with practical application in the field. This study was conducted at the Investment and One-Stop Integrated Service Office of Serang City, focusing on analyzing the implementation of partnership facilitation, investment achievements, encountered challenges, and efforts to enhance the effectiveness of investment activities. The method used is descriptive qualitative, with data collected through observation and interviews. The results indicate that partnership facilitation has been effective in strengthening cooperation between large businesses and SMEs, as well as supporting regional investment realization. However, some challenges remain, such as limited understanding, data access, and coordination. Efforts to overcome these challenges include improving communication, task comprehension, discipline, and continuous evaluation. This activity plays a crucial role in creating a conducive investment climate, promoting economic growth, and enhancing students’ competencies in facing the workforce.